Analisis Semiotika Roland Barthes Terhadap Isi Pesan Dakwah Iklan Pepsodent Siwak - Amran Al Bantani Azis; Muhammad N. Abdurrazaq; Irvan Iswandi (Tabsyir: Jurnal Dakwah dan Sosial Humaniora, 2024)
. In this era, globalization and information technology play a very important role in human life. Playing a role in selecting consumer products, people rely on technology and information media in selecting goods that suit their needs. This research aims to determine the content of the da'wah message in the Pepsodent Siwak advertisement and to determine the meaning of connotation and denotation in the Pepsodent Siwak advertisement. The research approach used by literature (library research) is descriptive qualitative and the analysis uses Roland Barthes' semiotic analysis method, regarding the content of the Pepsodent Siwak advertisement's Da'wah message. The research results show that: 1) the denotational meaning of the Pepsodent advertisement is that there is still a lack of awareness among Indonesian people about brushing their teeth morning and night, especially parents. Meanwhile, the connotation means that a father as a role model for children often does not set a good example for children, and this advertisement shows that there is more closeness between father and child. The myth that emerges is the closeness of boys to their fathers and the myth that adult men do not pay enough attention to dental and oral health. 2) The content of the da'wah message is divided into three dimensions, namely the faith dimension, the moral dimension and the sharia dimension. The specific social meaning and impact as a symbol of the message of Islamic da'wah in the Pepsodent Siwak advertisement in society is that it aims to seek salvation in the afterlife.